Weight Loss Instead of Weight Gain within the Guidelines in Obese Women during Pregnancy: A Systematic Review and Meta-Analyses of Maternal and Infant Outcomes. - Mufiza Zia Kapadia; Christina K Park; Joseph Beyene; Lucy Giglia; Cindy Maxwell; Sarah D McDonald (PLoS ONE)
Background Controversy exists about how much, if any, weight obese pregnant women should gain. While the revised Institute of Medicine guidelines on gestational weight gain (GWG) in 2009 recommended a weight gain of 5-9 kg for obese pregnant women, many studies suggested even gestational weight loss (GWL) for obese women. Objectives A systematic review was conducted to summarize pregnancy outcomes in obese women with GWL compared to GWG within the 2009 Institute of Medicine guidelines (5-9 kg). Design Five databases were searched from 1 January 2009 to 31 July 2014. The Cochrane Handbook for Systematic Reviews of Interventions and the PRISMA Statement were followed. A modified version of the Newcastle-Ottawa scale was used to assess individual study quality. Small for gestational age (SGA), large for gestational age (LGA) and preterm birth were our primary outcomes. Results Six cohort studies were included, none of which assessed preterm birth. Compared to GWG within the guidelines, women with GWL had higher odds of SGA <10th percentile (adjusted odds ratio [AOR] 1.76; 95% confidence interval [CI] 1.45-2.14) and SGA <3rd percentile (AOR 1.62; 95% CI 1.19-2.20) but lower odds of LGA >90th percentile (AOR 0.57; 95% CI 0.52-0.62). There was a trend towards a graded relationship between SGA <10th percentile and each of three obesity classes (I: AOR 1.73; 95% CI 1.53-1.97; II: AOR 1.63; 95% CI 1.44-1.85 and III: AOR 1.39; 95% CI 1.17-1.66, respectively). Conclusion Despite decreased odds of LGA, increased odds of SGA and a lack of information on preterm birth indicate that GWL should not be advocated in general for obese women.